2020
DOI: 10.1111/ijfs.14540
|View full text |Cite
|
Sign up to set email alerts
|

Extended preservation of raw beef and pork meat by hyperbaric storage at room temperature

Abstract: Summary Hyperbaric storage (HS) was evaluated as a new food preservation methodology at room temperature (RT) for beef and pork meat, both minced and in pieces, and compared to refrigeration (RF) storage. The meat samples were stored at 50, 75 and 100 MPa and variable RT up to 60 days. HS at 75 and 100 MPa could not only inhibit microbial growth but also inactivate microorganisms. Regarding physicochemical analyses, an overall equal to better pH maintenance in HS samples was achieved, and similar colour differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Protein solubility was an important indicator of protein properties, which was attributed to protein denaturation [ 37 ]. In this study, the results indicated that IN muscle had a high extent of protein denaturation after 9 days [ 19 ]. The solubility of myofibrillar protein increased with the aging period up to day 7 and then did not change significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein solubility was an important indicator of protein properties, which was attributed to protein denaturation [ 37 ]. In this study, the results indicated that IN muscle had a high extent of protein denaturation after 9 days [ 19 ]. The solubility of myofibrillar protein increased with the aging period up to day 7 and then did not change significantly.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are susceptible to oxidative degradation during aging, which may explain the meat tenderization after muscle fiber breakage [ 17 ]. Oxidation affects the chemical properties of proteins and changes in protein solubility can reflect the degree of protein denaturation [ 18 , 19 ]. Sarcoplasmic protein solubility (SPS) is sometimes used as a measure of muscle quality [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the feasibility to store fish/meat products under HS was studied for longer storage periods (up to 60 days), with promising results. Both food products revealed great microbial stability by HS above 50 MPa, with microbial reductions being verified in both endogenous and inoculated microorganisms . Thus, although HS at RT has proven its capability to control microbial growth, it is important to perform more insightful analysis in other important foods, such as milk, not only regarding the microbial quality but also the nutritional, physicochemical, and biochemical quality parameters, to gain further knowledge about the potential of HS to possibly substitute RF with prolonged shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that 75 and 100 MPa hyperbaric storage efficiently inactivated and eliminated microorganisms rather than simply inhibiting microbial growth. The study concluded that the drip loss of hyperbaric storage and refrigeration storage was similar (Santos, Delgadillo, & Saraiva, 2020).…”
Section: Meat and Marine Product Preservation By Hyperbaric Storagementioning
confidence: 99%
“…However, in recent years pressure preservation of food has become a sustainable alternative to high energy‐consuming, high carbon‐emitting preservation technologies. Numerous research findings are published in recent years suggesting a modification of ambient pressure as a preservation methodology for animal products like meat, fish, and milk (Duarte et al, 2015; Fernandes et al, 2019; Fidalgo et al, 2018, 2019, 2021; Fidalgo, Delgadillo, & Saraiva, 2020; Fidalgo, Simões, et al, 2020; Freitas et al, 2016; Santos, Castro, et al, 2020; Santos, Delgadillo, & Saraiva, 2020). Food industry is increasingly adopting high‐pressure processing (HPP) as a nonthermal pasteurization methodology to extend shelf‐life of the food products (Santos, Fidalgo, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%